Investment Amid Uncertainty: Exchange Rates and Oil Price Dynamics in Saudi Arabia - Abu Asab, Noura (International Journal of Energy Economics and Policy, 2024)
This study examines the impact of real effective exchange rates and oil price on private investment in Saudi Arabia, focusing on the role of economic uncertainty in this dynamic relationship. Using quarterly data from 2007 to 2022, this research applies the ARDL, error correction model, and nonlinear ARDL, to capture both short- and long-term effects. GARCH and EGARCH models assess the conditional variance, serving as indicators of economic uncertainty. The analysis reveals that oil prices and real effective exchange rates significantly enhance private investment in the long run, whereas exchange rate uncertainty proves to be negligible. Conversely, short-term volatility in oil prices has a pronounced negative effect. Notably, EGARCH findings indicate that positive exchange rate shocks induce greater subsequent conditional variance than negative shocks, while oil price shocks remain symmetric. The nonlinear ARDL model further shows that favorable exchange rate changes and elevated oil prices stimulate investment, highlighting the resilience of Saudi Arabia’s investment landscape. This research fills a critical gap by illustrating how the country’s fixed exchange rate system and oil production capacity mitigate external uncertainties, offering valuable insights for policymakers seeking to bolster economic stability in similar contexts.